Sastra Anak Sebagai Media Gerakan Literasi Budaya Pada Siswa Sekolah Dasar - Dewi Kusuma (Sekolah Tinggi Agama Islam Pati, 2022)
Children's literature is a literary work whose images and metaphors of life are told (feelings, thoughts and images) and the language used can be understood by children according to their level of mental development. In other words, children's literature is a literary work that uses a child's point of view in its storytelling. Children's literature can be created by children or adults as long as what is conveyed is still within the reach of the child's mental development. The benefits of children's literature are very diverse, one of which is that children's literature can be used to foster cultural literacy in elementary school students. Children's literature is a medium to instill students' understanding and love of Indonesian culture as a nation's identity. This study aims to determine how children's literature as a medium of cultural literacy movement in elementary school students. The research method used in this study is a qualitative descriptive method. Children's literature is literature created for children and has many benefits, including children's literature that can be used as a medium for cultural literacy. With literary works, students have an awareness of diversity which is the identity of their nation..